1991
DOI: 10.5465/ambpp.1991.4976867
|View full text |Cite
|
Sign up to set email alerts
|

Being Different: Relational Demography and Organizational Attachment.

Abstract: The results of the current study supported the general hypothesis that individuals who were different from others in a social unit on demographic attributes reported lower organizational attachment.However, contrary to the specific hypotheses on race and gender, the effect was stronger for whites and males than for non-whites and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
1,410
7
11

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 812 publications
(1,475 citation statements)
references
References 74 publications
42
1,410
7
11
Order By: Relevance
“…In response, members of a higher-status group may feel an urge to defend their group interest and deliberately exclude the lower-status group from promising opportunities within organizations. Consistent with this argument, research shows that increases in women's share within establishments enhance their male coworkers' feeling of being threatened, as well as the overall level of intergroup competition (Tolbert et al 1995; Tsui et al 1992), making men less supportive of women's career advancement (South et al 1987). …”
Section: Gender and Employment-status Compositions In The Workplacementioning
confidence: 88%
See 1 more Smart Citation
“…In response, members of a higher-status group may feel an urge to defend their group interest and deliberately exclude the lower-status group from promising opportunities within organizations. Consistent with this argument, research shows that increases in women's share within establishments enhance their male coworkers' feeling of being threatened, as well as the overall level of intergroup competition (Tolbert et al 1995; Tsui et al 1992), making men less supportive of women's career advancement (South et al 1987). …”
Section: Gender and Employment-status Compositions In The Workplacementioning
confidence: 88%
“…The study also utilizes the Japanese setting to address an understudied question: Does worker composition matter if the size of each social group has little impact on its relative status? Much of the previous research on workplace composition assumes that the effect of a social group's numerical representation on its life chances or well-being is mediated through the group's relative influence within establishments (e.g., Cohen et al 1998; Kanter 1977; Tolbert et al 1995; Tsui et al 1992). Within Japanese organizations, however, the gaps in status and power between standard and nonstandard employees, as well as between men and women, are unlikely to change according to the share of nonstandard employees or women.…”
mentioning
confidence: 99%
“…For example, Tsui, Egan, and O'Reilly (1992) suggested that the categorization process was "fundamental to the formation of in-groups and the widely documented tendency of individuals to prefer homogeneous groups of similar others" (p. 552, emphasis added). Williams and O'Reilly (1998, p. 119) reviewed over 40 years of diversity research and then arrived at a similar conclusion in noting that "it is clear that there are potentially negative consequences from social categorization processes operating in groups."…”
Section: Diversity and Categorizationmentioning
confidence: 97%
“…'', and if so, ''Are you worried that the symptoms you are experiencing may affect your ability to continue working?'' Difficulty with physical demands: assessed using the closedended question: ''On a scale from zero to five, with zero (0) being completely unable and five (5) [56], this measure captured participants' satisfaction with their work, pay, opportunity for promotion and relationships with their supervisor and coworkers. The scale included five items (scored 0-6), with low scores indicating low satisfaction.…”
Section: Rtw Durability Measuresmentioning
confidence: 99%